Corticosteroids in Pediatric Heart Surgery: Myth or Reality - Fudulu, Daniel P.; Gibbison, Ben; Upton, Thomas; Stoica, Serban C.; Caputo, Massimo; Lightman, Stafford; Angelini, Gianni D. (Frontiers in Pediatrics, 2018)
Background: Corticosteroids have been administered prophylactically for more than 60 years in pediatric heart surgery, however, their use remains a matter of debate. There are three main indications for corticosteroid use in pediatric heart surgery with the use of cardiopulmonary bypass (CPB): (1) to blunt the systemic inflammatory response (SIRS) induced by the extracorporeal circuit; (2) to provide perioperative supplementation for presumed relative adrenal insufficiency; (3) for the presumed neuroprotective effect during deep hypothermic circulatory arrest operations. This review discusses the current evidence behind the use of corticosteroids in these three overlapping areas. Materials and Methods: We conducted a structured research of the literature using PubMed and MEDLINE databases to November 2017 and additional articles were identified by cross-referencing. Results: The evidence suggests that there is no correlation between the effect of corticosteroids on inflammation and their effect on clinical outcome. Due to the limitations of the available evidence, it remains unclear if corticosteroids have an impact on early post-operative outcomes or if there are any long-term effects. There is a limited understanding of the hypothalamic-pituitary-adrenal axis function during cardiac surgery in children. The neuroprotective effect of corticosteroids during deep hypothermic circulatory arrest surgery is controversial. Conclusions: The utility of steroid administration for pediatric heart surgery with the use of CPB remains a matter of debate. The effect on early and late outcomes requires clarification with a large multicenter randomized trial. More research into the understanding of the adrenal response to surgery in children and the effect of corticosteroids on brain injury is warranted.